Degenerative Valvular Disease in the Cavalier King Charles Spaniel: Results of the UK Breed Scheme 1991–2010. (5th January 2017) - Swift, S.; Baldin, A.; Cripps, P.
Abstract : Background: Cavalier King Charles spaniels (CKCSs) are predisposed to degenerative mitral valve disease (DMVD) and studies have indicated a genetic cause. Animals: A total of 8, 860 CKCSs were examined at shows or private clinics from 1991 to 2010. Objectives: To analyze the effects of a breed scheme for CKCS on the age at which a murmur consistent with DMVD was first detected. Methods: The presence or absence of a murmur consistent with mitral regurgitation was noted and age a murmur was first detected recorded. Results: A total of 16, 887 examinations were performed on 8, 860 dogs. The median age dogs developed a murmur were slightly younger in male than female dogs (7.8 versus 8.3 years, 95% confidence interval [CI] 7.4–8.1 versus 8.0–8.4, P < .001) and cardiologists detected murmurs in younger dogs than did general practitioner (GP) veterinary surgeons (7.2 versus 8.6 years, 95% CI 7.0–7.4 versus 8.3–8.7 P < .001). In bitches examined by GP vets during the study, there was a significantly increased age of detection of murmurs over time (8.6–9.2 years, 95% CI 8.3–9.1 and 8.5–10.9, P = .001) but not for male dogs examined by GP vets or dogs of either sex examined by cardiologists. Conclusions and Clinical Importance: This study suggests that the age incidence of murmurs associated with DMVD might be increased by application of breeding guidelines based on auscultation alone. This benefit was only seen in a subgroup and compliance of breeders with this voluntary scheme was poor.